Manajemen Promosi Event Teenage Calling (Studi Kasus Keberhasilan Pengelolaan Promosi Kegiatan Mahasiswa Di Media Dalam Jaringan) - Andika Pramudya Ananta; Fariz D Septiansyah; Adinda Dwi Cahya; Mariana Rista Ananda Siregar (UNIVERSITAS PAKUAN, 2023)
Teenage Calling is a form of event organizer managed by a group of Pakuan University Communication Science students as one of the final assignment collections for special event management courses. This study aims to determine the success of promotional management at the teenage calling event in various online media. This research uses qualitative research methods with data collection techniques including interviews, observation, documentation of 3 in-depth sources, and literature studies. The results showed that promotion is the main key to the success of the event because promotion provides engagement with the event. The teenage calling event involves management functions, namely by implementing POAC so that an event runs smoothly, how the audience is interested in the event being held, and how to make an event interesting. Publication through online media is quite effective in this event considering that at the teenage calling event, the audience who came was so crowded that all tickets were sold out.